2010
DOI: 10.1111/j.1463-6409.2010.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic history of the butterfly subtribe Euptychiina (Lepidoptera, Nymphalidae, Satyrinae)

Abstract: Peña, C., Nylin, S., Freitas, A. V. L. & Wahlberg, N. (2010). Biogeographic history of the butterfly subtribe Euptychiina (Lepidoptera, Nymphalidae, Satyrinae).—Zoologica Scripta, 39, 243–258. The diverse butterfly subtribe Euptychiina was thought to be restricted to the Americas. However, there is mounting evidence for the Oriental Palaeonympha opalina being part of Euptychiina and thus a disjunct distribution between it (in eastern Asia) and its sister taxon (in eastern North America). Such a disjunct distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
127
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(145 citation statements)
references
References 61 publications
13
127
2
3
Order By: Relevance
“…The research on Euptychiina has struggled to show the monophyly of the group (Murray & Prowell 2005, Peña et al 2010. Again, it is believed that this is caused by problems of long branch attraction, particularly in Euptychia (Peña et al 2011), which is recognized as the sister group of the remaining members of the subtribe (Peña et al 2006(Peña et al , 2010.…”
Section: Marín Et Al From the Phylogeny Of The Satyrinae Bu Erfl Ies mentioning
confidence: 99%
See 4 more Smart Citations
“…The research on Euptychiina has struggled to show the monophyly of the group (Murray & Prowell 2005, Peña et al 2010. Again, it is believed that this is caused by problems of long branch attraction, particularly in Euptychia (Peña et al 2011), which is recognized as the sister group of the remaining members of the subtribe (Peña et al 2006(Peña et al , 2010.…”
Section: Marín Et Al From the Phylogeny Of The Satyrinae Bu Erfl Ies mentioning
confidence: 99%
“…This clade is recovered in various phylogenetic studies (Peña et al 2006, Peña & Wahlberg 2008, Wahlberg et al 2009 with partially resolved relationships and only supported by molecular characters (Fig 2) [ (Peña et al 2006, Peña & Wahlberg 2008 The lack of resolution in the topology of Satyrini is This phenomenon occurs in most of the subtribes of Satyrini (Peña et al 2011) and has been recently reported in Coenonymphina (Kodandaramaiah et al 2010a), Euptychiina (Peña et al 2010) and Mycalesina (Kodandaramaiah et al 2010b). Peña et al (2011) ind that the initial selection of Haeterini as outgroup for Satyrini produces unstable trees where Euptychia (Euptychiina) appears outside of Satyrini.…”
Section: Evoluti Onary Relati Onships Within Satyrinaementioning
confidence: 99%
See 3 more Smart Citations